Pengaruh Perceived Value, Price, dan Product Quality Terhadap Customer Loyalty Sepatu Nike - Kaysa Istifaus Shofi; Agus Abdurrahman (Journal Economic Excellence Ibnu Sina, 2023)
The aim of this research is to: influence Perceived Value, Price and Product Quality on Customer Loyalty for Nike Shoes. The sample in this study consisted of 110 respondents who had purchased and used Nike shoes for at least 3 years. The research method used is descriptive analysis with a quantitative approach. The test uses the SPSS v.25 analysis tool by conducting multiple regression analysis, hypothesis testing (t test and F test) to find out how perceived value, price and product quality influence customer loyalty among Nike shoe users